Micropolitics and Credibility of Barangay Officials (International Journal of Scientific Research and Management (IJSRM), 2023)
This study was conducted to determine the significant relationship between micro politics and the credibility of the barangay officials it also aimed to determine the domain of micropolitics that best predicts credibility of the barangay officials in the Island Garden City of Samal. The study is a non-experimental quantitative study that applied the descriptive-correlational technique. There were 381 respondents selected through stratified sampling. Data derived from the standardized survey was subjected to statistical testing and analysis using the mean and standard deviation, Pearson r, and regression analysis. Results showed an overall high level of micropolitics and a moderate level of credibility among barangay officials. Moreover, the correlation test yielded a robust, positive, and significant relationship between micropolitics and credibility. Furthermore, it was revealed that the domain sincerity best predicts credibility of barangay officials.